Symptom Similarities and Differences in Anxiety and Depressive Disorders - Dilek Sirvanli Ozen; Elif Temizsu (Psikiyatride Güncel Yaklaşımlar, 2010)
The question if there is a valid distinction between depression and anxiety disorders remains controversial. These two disorders have various overlaps in the symptomatology and sometimes it is difficult to make a clear diagnosis. The difficulty in making a definite diagnosis destined researchers to determine the differences and the similarities between anxiety and depression. The negative affect which has multiple dimensions such as low self-esteem, negative mood and negative cognitions is seen as the common factor in both disorders. The positive affect which has been defined as the harmony and satisfaction with others and milieu, is regarded as the discriminating factor for the diagnosis of depression. Further research has characterized somatic arousal as the third dimension, a candidate to be the discriminating factor for anxiety disorders. Although phenotypic models appear to find a solution for this problem the facts that negative affect dimension is more loaded compared to the other two dimensions and predominance of negative affect on several symptom patterns prevent researchers to reach a conclusive results regarding the differences between these two disorders. In this review article, symptom similarities and differences of anxiety and depressive disorders are discussed within the frame of phenotypic models and some alternative ideas are provided for possible changes in upcoming versions of classification systems.